The Influence of Financial Literacy and Consumptive Behavior on Indebted Behavior of Housewives - Siti Revina Agustine; Mardiana Mardiana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The increase in economic development has led to a rise in household needs, particularly in consumptive and lifestyle aspects. Unfortunately, this trend often overlooks individuals' financial conditions, compelling them to rely on debt as a means to fulfill unmet needs. Consequently, this behavior becomes ingrained and habitual. This article aims to explore the impact of financial literacy and consumptive behavior on the indebtedness of housewives who generate their own income. To achieve this objective, the study adopts a descriptive quantitative approach. The target population consists of housewives residing in Purwodadi Village, Blimbing District, Malang City, who possess their own source of income and have incurred consumer debt. Probability sampling techniques, coupled with the Slovin formula, are employed to select the sample. Data analysis is conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.0 software. The analysis comprises both outer model and inner model analyses. The findings of this study reveal that financial literacy exerts a positive and significant influence on debt behavior. This is evidenced by a t-statistic value of 3.984, exceeding 1.96, and a p-value below 0.05. Similarly, consumptive behavior demonstrates a positive and significant impact on debt behavior, supported by a t-statistic value of 7.094, surpassing 1.96, and a p-value below 0.05. In conclusion, the research findings indicate that both financial literacy and consumptive behavior significantly contribute to the indebtedness of housewives with independent income. By understanding the implications of these factors, policymakers, financial institutions, and individuals can develop strategies to promote responsible financial management and mitigate excessive debt accumulation among this specific demographic.